Percutaneous closure of coronary artery fistula: long-term follow-up results - Ilkay, Erdogan; Celebi, Ozlem Ozcan; Kacmaz, Fehmi; Ozeke, Ozcan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Coronary artery fistula consists of abnormal congenital connections between a coronary artery and cardiac chambers, a coronary vessel or an intrathoracic vessel that can be complicated by intracardiac shunts, endocarditis, myocardial infarction, or coronary aneurysms. Recent reports have emphasized the efficacy of percutaneous transcatheter techniques as an alternative to surgical closure, but the reported experience is relatively limited. Aim : To assess angiographic outcomes in a series of 20 patients who underwent transcatheter closure of coronary artery fistula. Material and methods : We evaluated all patients presenting with significant coronary artery fistula and undergoing transcatheter closure with coils and a vascular plug between March 2008 and June 2012. Results : There were 20 patients (14 men; mean age: 53 ±8 years) with coronary artery fistula. Fistula diameter ranged from 4 to 12 mm; an average of three coils were used in the percutaneous procedure. Post-deployment angiograms demonstrated complete occlusion in all patients. The patients were followed up for 4 ±1.6 years. The control coronary computed tomographic angiography was performed in the sixth month and no patients had recanalization of the embolized vessel. Conclusions : Percutaneous closure of coronary artery fistula is a safe and effective treatment modality.